Expiratory braking defines the breathing patterns of asphyxiated neonates during therapeutic hypothermia - Papoff, Paola; Caresta, Elena; D’Agostino, Benedetto; Midulla, Fabio; Petrarca, Laura; Giannini, Luigi; Pisani, Francesco; Montecchia, Francesco (Frontiers in Pediatrics, 2024)
Abstract Introduction: Although neonatal breathing patterns vary after perinatal asphyxia, whether they change during therapeutic hypothermia (TH) remains unclear. We characterized breathing patterns in infants during TH for hypoxic-ischemic encephalopathy (HIE) and normothermia after rewarming. Methods: In seventeen spontaneously breathing infants receiving TH for HIE and in three who did not receive TH, we analyzed respiratory flow and esophageal pressure tracings for respiratory timing variables, pulmonary mechanics and respiratory effort. Breaths were classified as braked (inspiratory:expiratory ratio≥1.5) and unbraked (<1.5). Results: According to the expiratory flow shape braked breaths were chategorized into early peak expiratory flow, late peak expiratory flow, slow flow, and post-inspiratory hold flow (PiHF). The most braked breaths had lower rates, larger tidal volume but lower minute ventilation, inspiratory airway resistance and respiratory effort, except for the PiHF, which had higher resistance and respiratory effort. The braked pattern predominated during TH, but not during normothermia or in the uncooled infants. Conclusions: We speculate that during TH for HIE low respiratory rates favor neonatal braked breathing to preserve lung volume. Given the generally low respiratory effort, it seems reasonable to leave spontaneous breathing unassisted. However, if the PiHF pattern predominates, ventilatory support may be required.